Injury incidence, patterns, and severity in cameroon professional Men’s Football: A prospective injury surveillance study - Gilbert Mua Akwa; Tankeng Leonard Tanko; Njowe Serge Ludwig; Ange Veronique Ngo Bilong; Nana Chunteng Theophile (PLoS ONE, 2026)
Background Football injuries are a major source of morbidity among athletes, imposing health and economic burdens on teams and systems. While extensive surveillance exists in Europe, data from sub-Saharan Africa remain scarce. This study described the incidence, patterns, severity, and contextual factors of match-related injuries among professional male footballers in Cameroon. Methods A prospective cohort design was conducted during the 2023/2024 Cameroon Elite 1 and Elite 2 league playoff tournaments. Match-day medical officers recorded all medical-attention injuries using standardized consensus-based forms [1]. Injury incidence was calculated per 1,000 player-hours, and descriptive analyses summarized injury characteristics. Ethical approval was obtained from the University of Douala and authorization from the Cameroon Football Federation. Results Across 139 matches, 171 injuries were recorded giving an incidence of 37.3 per 1,000 player-hours. Elite 2 players had more than double the rate of Elite 1 players (53.6 vs. 26.3). Lower-limb injuries (71.9%) predominated, mainly affecting the thigh (33.9%) and lower leg (17.5%). The most common diagnoses were cramps (20.5%), contusions (19.9%), and sprains (17.5%). Severe injuries (>28 days) represented 20.5%, with tears, fractures, and concussions most frequent. Nearly half injuries occurred in the final 30 minutes of play, and midfielders and attackers sustained 68% of all injuries. Conclusion This first surveillance study in Cameroon reveals a high match injury burden, particularly in lower-tier leagues. The late-match clustering supports fatigue-related mechanisms, emphasizing the need for targeted prevention focusing on conditioning, workload regulation, and medical readiness in African football.